Peran Pendidikan Islami dalam Membangun Karakter Siswa Mi Nurut Taqwa Bondowoso - Maksum, Ahmad Nawawi (Academicus: Journal of Teaching and Learning, 2023)
Moral decadence among Indonesia's younger generation must and urgently be overcome. One of them is by providing Islamic education to the younger generation since attending elementary school. From this background, there are two main study focuses, namely the application of Islamic education at MI Nurut Taqwa Bondowoso and the role of Islamic education in building the character of students at MI Nurut Taqwa Bondowoso. This type of research uses qualitative methods with a descriptive pattern case study approach. This study also uses the theoretical framework of Islamic education and the theory of student character formation. This research came to the conclusion that 1) the implementation of Islamic education at MI Nurut Taqwa Bondowoso has been carried out according to the basic philosophy of Islamic education 2) The role of Islamic education is very crucial and determinant in shaping the character of students as well as building the character of the nation.